Tren Kepengarangan Berkala Ilmu Perpustakaan dan Informasi Periode 2014-2018: Sebuah Analisis Bibliometrik - Sri Junandi (Media Pustakawan, 2019)
This article discusses Bibliometrics which was used to analyse 80 articles published in journal Berkala Ilmu Perpustakaan dan Informasi (BIP) from 2014 to 2018 published by the Library of Universitas Gadjah Mada. This study aims to determine the distribution of articles per year as well as per number, authorship patterns, type of references used, institutional contribution and author productivity. The data was downloaded from the https://jurnal.ugm.ac.id/bip, and was processed using Microsof Excel 2013, as well as the degree of collaboration calculated in the Subramanyam formula. The results showed that BIP has published a total of 80 articles involving 120 people authors, with a single author larger than the multiple author; collaboration degrees value at 0.67. The majority of the references used were textbooks (65.15%) and scientific journals (31.04%). Affiliate authors come from educational institutions is the biggest contributor article, and Gadjah Mada University is in the first order (36 times). Female authors are more productive than male authors: Pergola Irianti served as the first one (4 articles). Some suggestions include that a journal manager should increase the number of collaborative authors and to require that published articles should have 80% of the journals and the proceedings as the main reference.